Immunodepression after CPB: Cytokine dynamics and clinics after pediatric cardiac surgery – A prospective trial. (October 2019) - Justus, Georgia; Walker, Christoph; Rosenthal, Lisa-Maria; Berger, Felix; Miera, Oliver; Schmitt, Katharina Rose Luise
Highlights: Corrective surgery with CPB causes a transient immunodepression. Cardiosurgical trauma triggers downregulation of TNF-α and IL-6 independently from CPB and operation time. Immunodepression as defined as monocytic unresponsiveness to LPS takes place simultaneously with inflammatory reaction. IL-10, IL1-Ra and MCP-1 are still produced during depression and overly secreted during reversion. Suppression of TNF-α is associated with longer mechanical ventilation. Abstract: Background: Corrective surgery for congenital heart defects is known to trigger a severe immune reaction. There has been extensive research on the effects of inflammation after cardiopulmonary bypass (CPB). Interestingly, monocytes are observed to be non-responsive to stimulation with lipopolysaccharide (LPS) under these conditions, indicating a state of immunodepression, which lays the ground for second hit infections after cardiosurgery with CPB. Objectives: The aim of this prospective study was to analyze immunodepression after pediatric cardiopulmonary bypass and to differentiate the effects of monocytic anergy on postoperative outcome. Methods: In a prospective trial, we quantified the immune responses in 20 pediatric patients (median age 4.9 months, range 2.3–38.2 months; median weight 7.2 kg, range 5.2–11.7 kg) with congenital ventricular septal defect undergoing heart surgery with CPB. Ex vivo LPS-induced protein expression of IFN-γ, IL-1β, IL-1Ra, IL-6, IL-8, IL-10, IL-12, IL-17, TNF-α, and MCP-1 was measured before (T1), immediately after (T2) and 4 h after (T3) cardiopulmonary bypass surgery using Luminex technology. Results: The innate immune system responds to CPB with an almost complete depression of monocytic function. Inflammatory IL-12, TNF-α, IL-1β, IL-6, IL-8 and IFN-y are completely suppressed. IL-10, IL-1Ra and MCP-1 are still produced during suppression with IL-1Ra being overly secreted during reversion. Suppression of TNF-α expression after LPS-stimulation correlates closely with longer mechanical ventilation time (r = −0.619, p = 0.004). Conclusion: Cardiosurgery with CPB causes a state of immunodepression making pediatric patients more vulnerable to second hit infections. MCP-1, IL-10, and IL-1Ra play an important role in monocyte recovery, eventually permitting new therapeutic options for controlling immunodepression and inflammation. Standardized glucocorticoid therapy should be evaluated carefully for each individual patient.